Public et privé dans l’enseignement supérieur au Mexique - Sylvie Didou-Aupetit (Cahiers de la Recherche sur l'Education et les Savoirs)
Private Higher Education in Mexico has grown rapidly in the past two decades. The expansion has produced institutional diversification: the non public sector is dominated by small and isolated institutions, operating outside quality assurance frameworks and prestigious universities’ networks. Their profiles and their development strategies are utterly heterogeneous. One of the main issues for governmental authorities is therefore to regulate the sector in a context marked by high selectivity and low enrolments in public universities. Given the complexity of the political and social interests at stake, the lack of qualitative research on private higher education appears problematic, both in terms of knowledge and governance.